The effectiveness of the Clear ARCS motivational model in learning the skill of bottom-facing volleyball for students - Saeed Gheni Noori /Falah kadhim Dhaigham ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research is summarized in the preparation of educational units according to the CLEAR ARCS motivational model in the positive interaction between the teacher and the learner according to the four stages, namely (raising attention, linking the connection, the stage of confidence and the stage of satisfaction), which contributed to the speed of learning the skill of sending with volleyball. The research sample was determined from the second stage students in the College of Physical Education and Sports Sciences at Dhi Qar University for the academic year 2020-2021, whose number is (92) students, and (30 students) were selected randomly as a sample for the research by (12) students for each of the two groups ( The control and experimental group) and (6 students) for the pilot sample, and the researchers used the experimental approach with two equal groups, and the researchers concluded that the superiority of the experimental group over the control group due to the effectiveness of applying the stages of the CLEAR ARCS motivational model in the educational units of the experimental group, and the researchers recommended the necessity of applying this Model for the rest of the basic skills of volleyball and other games.